Global Signal Topography of the Human Brain: A Novel Framework of Functional Connectivity for Psychological and Pathological Investigations - Ao, Yujia; Ouyang, Yujie; Yang, Chengxiao; Wang, Yifeng (Frontiers in Human Neuroscience, 2021)
The global signal, which was once regarded as a nuisance of functional magnetic resonance imaging, has been proved to convey valuable neural information. This raised the question: how does global signal represent in local brain regions? In order to answer this question, the global signal topography was developed to measure the correlation between global signal and local signals. It was observed that the global signal topography has an intrinsic structure characterized by higher global signal correlation in sensory cortices and lower global signal correlation in higher-order cortices. The global signal topography could be modulated by individual factors, attention-demanding tasks, and conscious states. Furthermore, abnormal global signal topography has been uncovered in patients with schizophrenia, major depressive disorder, bipolar disorder, and epilepsy. These findings provide a novel insight into understanding how the global signal and local brain signals coactivate to organize information in the human brain under various brain states. Future directions were further discussed, including the local-global confusion embedded in the global signal correlation, the integration of spatial information conveyed by the global signal and temporal information recruited by the connection analysis. Overall, a unified psychopathological framework is needed for understanding the global signal topography.